2015
DOI: 10.1111/ijcs.12253
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ intention to buy protected designation of origin and protected geographical indication foodstuffs: the case of Greece

Abstract: There is evidence that consumers tend to highly regard the quality, authenticity, ethical standards, country of origin and sustainable production of foodstuffs; hence, the growing number of studies on products of Protected Designation of Origin (PDO) and Protected Geographical Indication (PGI). PDO and PGI labelling is associated with the preservation of local plant varieties, the financial reward of local people and the sustainable development of rural areas. This study was set out to investigate the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 25 publications
0
59
0
9
Order By: Relevance
“…A comparative study of 12 food values between the United States and Norway using the best-worst scaling approach showed that respondents in both countries have similar food values, with safety being scaled as the most important value and nutrition ranked 6th [12]. Moreover, various studies on consumers' "willingness to pay" (WTP) have reported that PDO regional products are highly appreciated [13][14][15] and are perceived by consumers as healthier [16]. Other studies have reported that consumers expect that products with nutrition and health claims on the packaging have a better overall nutritional value compared with products without such information [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of 12 food values between the United States and Norway using the best-worst scaling approach showed that respondents in both countries have similar food values, with safety being scaled as the most important value and nutrition ranked 6th [12]. Moreover, various studies on consumers' "willingness to pay" (WTP) have reported that PDO regional products are highly appreciated [13][14][15] and are perceived by consumers as healthier [16]. Other studies have reported that consumers expect that products with nutrition and health claims on the packaging have a better overall nutritional value compared with products without such information [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Három olasz nagyvárosban végzett hasonló felmérés alapján az olasz válaszadók 37,4 százaléka állította magáról azt, hogy az OEM-címkével kapcsolatban jó vagy kiváló ismeretekkel rendelkezik (Vecchio-Annunziata [2011]). Egy Athén környéki felmérésben mind az OEM-, mind pedig az OFJ-címkék szubjektív ismeretét vizsgálták, és közöttük nagy volt a különbség, ugyanis az előbbi címkét a válaszadók mintegy 70, az utóbbit körülbelül 40 százaléka ismerte (Likoudis et al [2016]).…”
Section: Tárgyszóunclassified
“…Com o aumento da valorização de produtos por sua qualidade, auten cidade, local de origem, entre outros, por parte do consumidor (LIKOUDIS et al, 2016), há também maior necessidade de regulamentação das IGs, tanto em âmbito nacional como internacional. De acordo com a World Intellectual Property Organiza on (WIPO), as IGs atestam que um produto tem um local específi co de origem e apresenta qualidade ou reputação ligada a esse local.…”
unclassified
“…Com base em Porter (1986) e Hi , Ireland e Hoskisson (2003), a estratégia de diferenciação pode ser compreendida como inves mentos con nuos na criação e desenvolvimento de caracterís cas que diferenciam um bem ou serviço em formas que o cliente valoriza, atendendo assim às necessidades únicas dos clientes. Verifi ca-se que os consumidores estão demandando por produtos de alto valor agregado com caracterís cas específi cas, formando um mercado segmentado (ZYLBERSZTAJN et al, 2001;SOUZA, 2004;NIEDERHAUSER et al, 2008;LIKOUDIS et al, 2016). A estratégia de diferenciação pode estar relacionada aos atributos de qualidade da bebida, origens e às questões ambientais e sociais.…”
unclassified
See 1 more Smart Citation